PARTICLE SIZE CHARACTERISTICS OF RIVERBED SEDIMENTS TRANSPORTED BY TIDAL BORE âBONOâ IN KAMPAR ESTUARY, RIAU-INDONESIA - Gemilang, Wisnu Arya; Wisha, Ulung Jantama; Rahmawan, Guntur Adhi (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2018)
The presence of tidal bore in the Kampar River (locally known as âbonoâ) may influence sedimentation in the Kampar River and its estuary. Understanding sedimentation mechanisms (e.g., erosion, deposition) is important to communities along the Kampar River, which can be studied by analyzing characteristics of grain size distribution. Here, we study riverbed sediment samples collected from 17 stations using an Ekman grab sampler, accompanied by bathymetry and acoustic Doppler current profiler (ADCP) measurements. Grain size data show that the sediments are coarser upstream and gradually finer downstream. Silty sands are predominant in the upstream section of the river, sands in its river body and sandy silts in the downstream. The results indicate the influence of undular bores on grain size characteristics. We also found that the propagation of bono and Kampar Riverâs funnelshaped morphology cause intense scouring events of riverbed sediments. Sortation values that range between 0.332.14 suggest unstable currents that result in randomly deposited sediments. The sediment mass transfer per area is positively towards downstream at the low tidal condition. However, after the passage of the bores, the sediment mass transfer area becomes negatively towards upstream.